Exploring Post-Epidemic Marketing Strategies in Higher Education: A Synthesis of Recent Research and Implications (Orchid Insights: A Multidisciplinary Journal of Orchid College, 2025)
The increasing number of competitors, commodification of educational value and globalization has pressured those providers to adapt different marketing strategies. This study aimed to explore the marketing activities using 7Ps framework and six-phase thematic analysis to understand what activities influence the post-pandemic enrollment decisions in HEIs. In this regard, this paper uses the six-phase thematic analysis to review the discussion session from the 11 articles published between 2022 and 2024. This paper shows the shift of marketing activities from program, price, place, promotion, people, process, and physical evidence to post-pandemic practice including managerial practices, facilities, financial considerations, programs’ feature, branding and media exposures, These are aligning with student needs, program quality and affordability. This study concludes that HEIs must balance both traditional and post-pandemic strategies to enhance students’ experience.